1995
DOI: 10.1002/mrm.1910340105
|View full text |Cite
|
Sign up to set email alerts
|

The use of a priori knowledge to quantify short echo in vivo1h mr spectra

Abstract: In vivo 1H MR spectra of the prefrontal cortex acquired with the stimulated echo acquisition mode (STEAM) TE = 20 ms sequence were quantified to determine relative levels of cerebral metabolites. A priori knowledge of spectra from individual metabolites in aqueous solution was incorporated into a frequency domain quantification technique. The accuracy and precision of modeling these metabolites were investigated with simulated spectra of varying signal-to-noise ratios (SNRs) and relative metabolite levels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 39 publications
(29 reference statements)
1
104
0
1
Order By: Relevance
“…The values obtained for the main peaks and metabolite ratios are within the range of previously reported test/retest reproducibility for 1 H MRS measures in the in vivo human brain (Bartha et al 2000;Bertolino et al 1998;Brooks et al 1999;Charles et al 1996;Marshall et al 1996;Schirmer and Auer 2000), suggesting that the baseline variability of these measures is in the low to moderate range. The variability of NAA, PCrϩCr, TMA, and INO brain concentrations in healthy individuals and schizophrenic patients has been well-documented in several studies (Bartha, et al 2000;Bertolino et al 1998;Brooks et al 1999;Charles et al 1996;Marshall et al 1996;Michaelis et al 1993;Schirmer and Auer 2000;Stanley et al 1995). Overall, the changes in the various 1 H MRS human brain metabolites after lorazepam administration found in our study were similar to previously reported values for test/restest reproducibility of 1 H MRS measures, suggesting that acute lorazepam administration does not have specific effects on the main peaks that are part of the in vivo human 1 H MRS brain spectra.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The values obtained for the main peaks and metabolite ratios are within the range of previously reported test/retest reproducibility for 1 H MRS measures in the in vivo human brain (Bartha et al 2000;Bertolino et al 1998;Brooks et al 1999;Charles et al 1996;Marshall et al 1996;Schirmer and Auer 2000), suggesting that the baseline variability of these measures is in the low to moderate range. The variability of NAA, PCrϩCr, TMA, and INO brain concentrations in healthy individuals and schizophrenic patients has been well-documented in several studies (Bartha, et al 2000;Bertolino et al 1998;Brooks et al 1999;Charles et al 1996;Marshall et al 1996;Michaelis et al 1993;Schirmer and Auer 2000;Stanley et al 1995). Overall, the changes in the various 1 H MRS human brain metabolites after lorazepam administration found in our study were similar to previously reported values for test/restest reproducibility of 1 H MRS measures, suggesting that acute lorazepam administration does not have specific effects on the main peaks that are part of the in vivo human 1 H MRS brain spectra.…”
Section: Discussionmentioning
confidence: 93%
“…The list of 1 H metabolites utilized in our analyses, based on prior knowledge, included NAA, PCr ϩ Cr, INO, scyllo-Inositol, TMA, Glu, Gln, alanine, aspartate, lactate, taurine, and N-acetyl-aspartate glutamate (NAAG). Only the 1 H metabolites with reasonable precision for quantification (Stanley et al 1995) were reported in the results (i.e., NAA, PCr ϩ Cr, INO, TMA, Glu, Gln), and were expressed as absolute values, as well as ratios. The absolute metabolite levels (institutional units), which included the RF pulse amplitude and receiver gain corrections, and the volume correction for CSF (mean measurement value/1-CSF), excluded any T 1 and T 2 relaxation corrections, and were estimated relative to the phantom signal with a known metabolite concentration.…”
Section: H Mri/mrs Proceduresmentioning
confidence: 99%
“…Quantification of glutamate but not glutamine was possible. The water-unsuppressed signal was utilized to obtain absolute quantification values with units of mmol/kg wet weight as described by Stanley et al (1995). Grey and white matter tissue fractions were assumed to be constant for all subjects.…”
Section: H Spectroscopymentioning
confidence: 99%
“…More recently, Venkatraman et al 124 compared the precision (reproducibility) and variability of singlevoxel PRESS data collected from the anterior cingulate and hippocampus at 4.0 T with reproducibility (single subject scanned multiple times) [125][126][127][128][129][130][131][132][133] and variability studies (many subjects scanned at least once) 109,115,120,128 -130,134 -144 from the literature (many different regions of the brain). The motivation for the Venkatraman study was the review of Steen et al, 145 who found an average coefficient of variation (CV, % ϭ SD/mean ϫ 100) for NAA by Steen et al 145 in the frontal lobe in healthy controls of 13.7% at 1.5 T (from 16 published studies).…”
Section: Reproducibility Of Mrs Studies Of Normal Controlsmentioning
confidence: 99%